Analysis of task in school leaving mathematical examination in Lithuania between the two world wars - Ragalytė, Birutė; Paukštienė, Alma (Lietuvos matematikos rinkinys, 2010)
The school leaving mathematical examination in Lithuania between the two world wars is discussed in this article. Types of problems at the school-leaving mathematical examination (algebra, trigonometry, analysis) at this period are described. What mathematical knowledge needed to solve them is discussed.